Vaccination hesitancy as a cause of COVID-related mortality - Kılıç, Jehat; Yıldırım, M. Serdar; Alakuş, Ömer Faruk; Kiliç, Delyadil Karakaş; Y., Nurettin A.; Ebik, Berat (International Journal of Research in Medical Sciences, 2022)
Background: In this study, our aim was to draw attention to the vaccine hesitation as a cause of unvaccination and evaluate the vaccinated and unvaccinated patients in the intensive care unit in terms of morbidity and mortality. Methods: A hundred and ninety-nine patients between the May 2021-September 2021 admitted to the intensive care units in our hospital were included in this study. We included the patients with COVID-19 infection as assessed by reverse-transcriptase–polymerase-chain-reaction (RT-PCR) assay. Results: Despite the availability of eligible vaccines in our region, the most of included patients in this study were unvaccinated (n:119). Eighty patients were vaccinated. The vaccinated patients were divided into six groups according to their vaccination status such as subgroup 1: one-dose Coronavac, subgroup 2: two-doses Coronavac, subgroup 3: three-doses Coronavac, subgroup 4: 2-doses Coronavac+ One-dose BNT162b2, subgroup 5: one-dose BNT162b2, subgroup 6: two-doses BNT162b2 (Numbers of patients: 7-61-3-1-10-0 respectively for each group). Between the vaccinated and unvaccinated groups, there was no significant difference in terms of mortality (p>0,05). The majority of patients in the vaccinated group were the patients vaccinated with Coronavac (subgroup 2:59), and there was no full dose vaccinated patient with BNT162b2. Conclusions: While both vaccines are effective to reduce the morbidities and mortality related to COVID-19, there might not be efficacy in these vaccines, particularly Coronavac, following the admission to the intensive care unite in the more vulnerable population. And despite the availability of vaccines, vaccine-hesitancy may be one of the significant reasons for the hospitalization process.